Photon energy dependence of final state screening in a dilute electron gas system: A synchrotron radiation photoemission study of beta-PbO2 - Payne, D; Hu, J; Egdell, R; Dhanak, V; Miller, G (2007)
Photoemission spectra of thick films of β-PbO2 have been measured over a range of exciting photon energies between 40 eV and 150 eV. There is evidence for occupation of conduction band states above the top of the main valence band to give a degenerate electron gas and the spectra terminate in a sharp metallic Fermi edge. Structure associated with screening of shallow 5d core holes by the mobile conduction electrons observed in Al Kα excited X-ray photoemission spectra is suppressed in the lower energy spectra and the Pb 5d core level appears as a simple spin-orbit doublet. © 2007 Elsevier B.V. All rights reserved.